2012
DOI: 10.1111/j.1471-4159.2012.07900.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase‐3 in the central nervous system: a look on the bright side

Abstract: Matrix metalloproteinases (MMPs) are a large family of proteases involved in many cell-matrix and cell-cell signalling processes through activation, inactivation or release of extracellular matrix (ECM) and non-ECM molecules, such as growth factors and receptors. Uncontrolled MMP activities underlie the pathophysiology of many disorders. Also matrix metalloproteinase-3 (MMP-3) or stromelysin-1 contributes to several pathologies, such as cancer, asthma and rheumatoid arthritis, and has also been associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 129 publications
1
83
1
1
Order By: Relevance
“…The fact that PCLDs may progress through processes of survival, neovascularisation and loss of cell adhesion1–3 10 prompted us to study in vivo the expression of MMP-3, a metalloprotease reported to participate in all of these mechanisms 18. MMP-3 was found to be ∼4.5-fold and ∼35-fold overexpressed in polycystic human and rat cholangiocyte cultures, respectively (p < 0.0001; figure 1B and see online supplementary figure S3B), and is stimulated by both IL-8 and 17β-oestradiol in normal human cholangiocytes (see online supplementary figure S4B and S4D, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The fact that PCLDs may progress through processes of survival, neovascularisation and loss of cell adhesion1–3 10 prompted us to study in vivo the expression of MMP-3, a metalloprotease reported to participate in all of these mechanisms 18. MMP-3 was found to be ∼4.5-fold and ∼35-fold overexpressed in polycystic human and rat cholangiocyte cultures, respectively (p < 0.0001; figure 1B and see online supplementary figure S3B), and is stimulated by both IL-8 and 17β-oestradiol in normal human cholangiocytes (see online supplementary figure S4B and S4D, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…53 Interestingly, it has been reported that MMP-3 can be involved in normal CNS-remodelling and in the remyelination process, as shown by the strict spatiotemporal MMP-3 upregulation in the injured CNS, which may contribute to stem cell migration, neuroprotection and remyelination in the injured sites. 51 An involvement of MMP-3 in remyelination during the regenerative period after a CNS injury was demonstrated for the first time in the murine cuprizone-induced demyelination model. It was reported that not only during the early demyelination stage, but also during the stage of remyelination, MMP-3 was highly expressed in astrocytes of the corpus callosum.…”
Section: Metalloproteinase-3mentioning
confidence: 94%
“…50 It has been demonstrated that MMP-3 contributes to different pathological conditions, such as rheumatoid arthritis (RA), asthma, cancer and neurological disorders, including MS, Parkinson's disease (PD) and Alzheimer's disease (AD). 51 In MS, the increased circulatory level of MMP-3 correlates with disease activity in RRMS. This may contribute to the breakdown of the BBB at the time of relapse.…”
Section: Metalloproteinase-3mentioning
confidence: 99%
“…study of cultured mouse NG2 glia exposed to Il17 or Tnf [158] Neuronal and synaptic plasticity [159] Matrix Metalloprotease 9, MMP9…”
Section: Matrix Metalloprotease 3 Mmp3mentioning
confidence: 99%